Stem Cell Biology and Regenerative Medicine in Ophthalmology - Tsang, Stephen H.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana Press, 2013)
Patient specific and disease specific stem cell lines have already introduced groundbreaking advances into the research and practice of ophthalmology. This volume provides a comprehensive and engaging overview of the latest innovations in the field. Twelve chapters discuss the fastest growing areas in ophthalmological stem cell research, from disease modeling, drug screening and gene targeting to clinical genetics and regenerative treatments. Innovative results from stem cell research of the past decade are pointing the way toward practicable treatments for retinitis pigmentosa, age related macular degeneration, and Stargardt disease. What future directions will stem cell research take? Researchers, graduate students, and fellows alike will find food for thought in this insightful guide tapping into the collective knowledge of leaders in the field. Stem Cells in Ophthalmology is part of the Stem Cells in Regenerative Medicine series dedicated to discussing current challenges and future directions in stem cell research.
The Eye as a Target Organ for Stem Cell Therapy -- Stem Cells in Oculofacial Plastic Surgery -- The Current Status of Corneal Limbal Stem Cell Transplantation in Humans -- Lens Differentiation from Embryonic Stem (ES) and Induced Pluripotent Stem (iPS) Cells -- Stem Cells and Glaucoma -- Bone Marrow Stem Cells in Retinal Disease -- Stem Cells, Mechanism Based Therapies and Regenerative Medicine Approaches -- New Developments in Retinal Cell Transplantation and the Impact of Stem Cells -- Cancer Stem Cells in Uveal Melanoma -- Current Ex-vivo Gene Therapy Technology and Future Developments -- Stem Cell-Based Therapeutics in Ophthalmology: Application Towards the Design of Clinical Trials.
Keywords: Life sciences; Ophthalmology; Cytology; Stem cells; Life Sciences; Stem Cells; Cell Biology; Ophthalmology